The Impact of Trans Papua Road Infrastructure on Local Business Growth in Nduga Regency - Gay Murib; Holomoan Hutajudu; Elsyan R. Marlissa (LPPM STIE KRAKATAU, 2026)
Purpose: This study examines the impact of road infrastructure development on local business growth in Nduga Regency, Papua Highlands, Indonesia, and explores community perceptions of its economic benefits and its sustainability. Research Methodology: A qualitative descriptive approach, complemented by quantitative analysis (Likert scale), was used to gather primary data from 30 respondents in the Kenyam District, including micro and small entrepreneurs, traders, and community members. Five key informants from the Regional Public Works Agency (PUPR), Bappeda, and community leaders provided additional insights through interviews. Secondary data were obtained from official statistics and government documents from 2019 to 2024. Results: The results show consistently high community ratings across all economic impact indicators, with 83.33% of respondents rating income improvement as